2018
DOI: 10.1111/poms.12835
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Big Data to Balance New Key Performance Indicators in Emergency Physician Management Networks

Abstract: Managing emergency physicians is a complex task and has increasingly intensified with the recent consolidation of many emergency departments (EDs). Large‐scale physician groups are facing challenges in resource deployment and performance evaluation. To objectively evaluate physicians across facilities, we leverage big data from an emergency physician management network and propose data‐driven metrics using a large‐scale database consisting of 84 hospitals, 1,079 physicians, and 10,615,879 patient visits in 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…In our review, three included studies measured productivity using such indices [20][21][22]. A few published modelling studies have also developed similar productivity indices based on theoretical data [23][24][25]. Their use and implications in clinical practice remains to be studied.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In our review, three included studies measured productivity using such indices [20][21][22]. A few published modelling studies have also developed similar productivity indices based on theoretical data [23][24][25]. Their use and implications in clinical practice remains to be studied.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Moreover, the performance evaluation scheme of medical staff established by them can reflect the investment of labor value and meet the requirements of hospital personnel management in the new medical reform. (Foster et al 2018) used the big data method to analyze the factors affecting the work performance of hospital doctors, including income potential, number of patients, disease complexity, patient experience, etc., and concluded that the number of patients and basic complexity are the key factors determining the income potential, and the income potential is also positively related to the patient experience. (Ider et al 2011) discussed the game between performance appraisal and nosocomial infection report in Mongolian hospitals, and found that hospital employees would minimize the number of nosocomial infection cases reported as much as possible due to the penalty measures in performance appraisal, so they suggested replacing the original index of nosocomial infection prevention and control measures with the original index of nosocomial infection rate.…”
Section: Analysis Of Research Hotspotsmentioning
confidence: 99%
“…The surge in data availability, in conjunction with growing computer power, has allowed healthcare analytics tools, such as AI and machine learning, to play an expanding role in the advancement of healthcare. For example, machine learning is now used to inform diagnosis (Miotto et al 2018), make predictions (Finlay 2018), develop prescriptive treatment algorithms (Champagne et al 2018, Jameson andLongo 2015a), reduce readmissions (Liu et al 2018, Queenan et al 2019, and objectively evaluate physicians (Foster et al 2018) (see Guha and Kumar (2018) for an overview of how big data analytics has been applied in the healthcare domain and for a roadmap of future research). Moreover, health information exchanges, facilitated by technologies like blockchain (Babich and Hilary 2019), may lead to more efficient hSCs by minimizing transaction costs and wastes (e.g., fraud, counterfeits).…”
Section: Research Opportunities and Concluding Remarksmentioning
confidence: 99%